Liquid chromatography : fundamentals and instrumentation - Fanali, Salvatore; Haddad, Paul R.; Poole, C. F.; Schoenmakers, Peter J.; Lloyd, David (Engineer) (Elsevier Science, 2013)
A single source of authoritative information on all aspects of the practice of modern liquid chromatography suitable for advanced students and professionals working in a laboratory or managerial capacity. Chapters written by authoritative and visionary experts in the field provide an overview and focused treatment of a single topic. Comprehensive coverage of modern liquid chromatography from theory, to methods, to selected applications. Thorough selected references and tables with commonly used data to facilitate research, practical work, and comparison of results.